The Role of Gusdurian Peduli's Philanthropic Actions in Overcoming the Economic Turbulence of Communities Affected by COVID-19 - Zunaidi, Arif; Maghfiroh, Fachrial Lailatul; Mohd Azmi, Nurul Athirah (Universitas Darussalam Gontor, 2024)
The epidemic has had a considerable impact in some Indonesian areas, including Nganjuk and Kediri. In the midst of this economic crisis, the Gusdurian Peduli movement made a significant contribution to those in need, particularly those affected by the epidemic. The Gusdurian Peduli for COVID-19 Action is one of the community activities that helps with COVID-19 management. The Gusdurian Network's philanthropic targets are peripheral groups of people impacted by COVID-19 who are regarded as economically unable. This study employed a field research methodology, whereas this research approach was qualitative. The data used in this study was analyzed using inductive analysis, whereas the data collected was analyzed using descriptive analysis. According to the findings of this study, the Gusdurin Cares campaign plays an important role for people afflicted by COVID-19. It has alleviated the load on those affected by the uncertain economic volatility through its actions and donations.